FACTORS RELATED TO THE EVALUATION OF THE TODDLERS' GROWTH EARLY DETECTION PROGRAM AT TAMAN POSYANDU IN PUSKESMAS LAMONGAN - Roykhana Nabella Nur, Dita; Tirto Husodo, Besar; Nugraha P, Priyadi (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2018)
Abstract: The toddlers’ growth early detection program in Taman Posyandu (Integrated Health Service Post) is monitoring the growth of children under five years using KMS (Road to Health Cards) and monitoring the development of children under five years using the developmental stage of children under five and preschool children. Provided there is no stimulation given stimulation, the brain system will be less-developed leading to the decrease of brain function. This health problem may impair the quality of human resources in the future. The purpose of the research is to analyze the factors associated with the evaluation of the early detection program of toddlers’ growth at Taman Posyandu in Puskesmas (Public Health Center) Lamongan. The populations in this study are 98 Posyandu cadres in the Puskesmas Lamongan working area. This study used univariate and bivariate data analyses, and employed Chi Square test (significance level = 0.05) as the data analysis technique. The results showed that the early detection program ran well (58.2%). Most of the respondents were 48-65 years old (55.1%), highly educated people (67.3%), unemployment (5.2%), people receiving training (77.6%). Chi Square test showed that age (p = 0.026), training (p = 0.000), cadre incentive fund (p = 0,000), Posyandu infrastructure facilities (p = 0,000), manuals of Posyandu activities (p = 0.000) were the variables related to the program implementation. Moreover, the implementation is the variable related to the output range of the early detection program (0,015). Suggestion for this research is the necessity to conduct the training for the cadres to improve the ability to conduct this toddlers’ growth early detection program